PHARMACOGNOSTICAL EVALUATION AND ANTICONVULSANT ACTIVITY OF LEAVES OF DIPLOCYCLOS PALMATUS LINN - MAHANTHESH M.C,; JALALPURE S.S, (International Journal of Pharma and Bio Sciences, 2015)
Diplocyclos Palmatus Linn (shivalingee) is widely used medicinal plant. The present study reveals the pharmacognostical characteristics of leaves of Diplocyclos Palmatus. The chloroform, alcoholic and aqueous extracts of the dried leaves were screened for the presence of chemical constituents using HPTLC and GCMS techniques, also screened for acute toxicity and anticonvulsant activity, against MES and PTZ convulsions, using Wistar albino rats. Phytochemical screening reveals the presence of maximum chemical constituents in chloroform extract followed by alcoholic and aqueous extract. We found no significant changes in average body weight of animals, up to tested oral dose of 3000 mg/kg. The in vivo study reveals the anticonvulsant activity of chloroform and alcoholic extract. The chloroform extract is found to be more potent, similar to Phenytoin, in controlling both MES and PTZ convulsions than alcoholic and aqueous extracts. Further studies were needed to identify the active constituent responsible in controlling convulsions. Also, our study suggests the application of Diplocyclos palmatus leaves in the treatment of convulsive disorders as a need of modern health science.